From Growing to Biology Plants 1e - Hacisalihoglu, Gokhan (Open textbook library., 2021)
Ready to find out how plants are grown and function? Take a fantastic voyage through plants. From Growing to Biology: Plants 1e brings the latest information for understanding of traditional and modern plant growing, form, and production. Topics covered in 30 chapters include concise and up-to-date ‘big picture’ infographics, student learning outcomes (SLOs), key vocabulary, assessment, as well as identification of 120 species, and more. Moreover, author Dr. G. Hacisalihoglu emphasizes on leaning concepts, binding those concepts together with visuals approach to make learning faster and more memorable. From Growing to Biology: Plants 1e is packed full of horticultural information that is ideal for both academia and industry growers. It is basic enough that if you are just getting started learning plants, you will be able to catch up. Always remember that practice makes permanent and keep going to take your learning plant bio to new levels.